Promoted peroxymonosulfate activation into ferrite sites over perovskite for sunset yellow degradation: Optimization parameters by response surface methodology - Tuna, Ozlem; Şimsek, Esra Bilgin (Elsevier, 2023)
The purpose of this research is to show the potential of CeFeO3 (CFO) perovskite as photocatalysts in PMSactivated AOPs for the degradation of target molecules. CeFeO3 photocatalyst was synthesized via a simple precipitation method. The structural, morphological and optical properties of the perovskite were characterized by XRD, SEM-EDS, and UV-vis diffuse reflectance analyses. Furthermore, the degradation efficiency of sunset yellow (SY) was investigated through batch experiments under different parameters (catalyst dosage, PMS concentration and initial dye concentration) and the results were optimized by applying Box-Behnken design method. The decomposition reaction was optimized in the presence of 0.49 g/L of catalyst dosage, 4.73 mM of PMS amount and 14.02 mg/L of dye concentration, with the degradation efficiency of 91.8%. It was observed that O2 & BULL;? , OH & BULL;, and SO4 & BULL;- played dominant role in reaction. Furthermore, CFO particles were sufficiently incorporated with different carbon materials (graphitic carbon nitride (g-C3N4), carbon fiber (CF) and N-doped carbon quantum dots (NCQDs)), showing excellent removal efficiency. This research shows inspiration for the treatment of polluted water with CeFeO3 under the synergistic effect of PMS and photocatalysis.
Keywords: Perovskite; Sunset; Photocatalyst; Peroxymonosulfate